Numerical simulation of arterial flow with moving boundaries - Siauw, Wei Long. (2008)
The objective in the research is to study the oscillatory nature of wall shear stress (WSS) as a result of a pulsatile flow and periodically excited wall. In the first stage of the research, a non-Newtonian incompressible Navier-Stokes (N-S) solver has been developed using Fasttalk language within the Fastflo environment. It is based on the method of operator splitting and method of artificial compressibility. Code validation for the developed Newtonian model has been performed on two different geometries of a backward facing step at two Reynolds numbers of 50 and 150 to serve as a basis for modification to the non-Newtonian model. The Power Law and Casson models have been used as the constitutive equations for blood with a hematocrit of approximately 45%. These two non-Newtonian models and the Newtonian model are used to simulate unsteady flow through a hypothetical stenotic geometry over a time interval of one second. Unsteadiness is introduced by subjecting the inlet to an aperiodic pressure wave depicting a "systolic" and "diastolic" like effect. Through the comparison of the results of the three models, it is found that the WSS distribution one second is comparable for both non-Newtonian models and is oscillatory in nature. The peak WSS for the Newtonian model has the lowest value.